2002
DOI: 10.1080/09593332308618359
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Municipal Primary Sludge: Effect of Srt and Solids Concentration on Volatile Fatty Acid Production

Abstract: Laboratory bench-scale experiments were conducted to investigate the performance of primary sludge fermentation for volatile fatty acids production. Primary sludges from two major wastewater treatment plants located in Valencia (Pinedo and Carraixet) were used. Experiments were performed at solids retention times between 4 and 10 days, and total volatile solids concentrations between 0.6% and 2.8%. Operation at two temperatures (20 degrees C and 30 degrees C) was also checked. Results indicated the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…The digester effluent (total VFAs equalling 3153 mg/L as HAc), contained mean concentrations of 1621 mg/L HAc (51.4%), 1071 mg/L HPr (27.5%), 909 mg/L n-HBu (19.6%) and 75 mg/L i-HVa (1.4%). In general, the distribution of HAc and HPr was relatively consistent with other researchers operating at similar SRTs, where HAc ranged from 33% to 73% and HPr from 22% to 44% (Mavinic et al 2000;Bouzas et al 2002).…”
Section: Resultssupporting
confidence: 89%
“…The digester effluent (total VFAs equalling 3153 mg/L as HAc), contained mean concentrations of 1621 mg/L HAc (51.4%), 1071 mg/L HPr (27.5%), 909 mg/L n-HBu (19.6%) and 75 mg/L i-HVa (1.4%). In general, the distribution of HAc and HPr was relatively consistent with other researchers operating at similar SRTs, where HAc ranged from 33% to 73% and HPr from 22% to 44% (Mavinic et al 2000;Bouzas et al 2002).…”
Section: Resultssupporting
confidence: 89%
“…Miron et al (2000) found that digestion of primary sludge at 25°C resulted in methanogenic conditions for SRT over 8 days. Bouzas et al (2002) also showed that the VFA production was reduced significantly below 4-day SRT and increased slightly over 6-day SRT. The optimum treatment time for VFA production was obtained at fermentation time of 6 days in batch fermentation experiments performed by Jiang et al (2007) for waste activated sludge.…”
Section: Final Discussionmentioning
confidence: 86%
“…The applicability of primary sludge hydrolysis to produce volatile fatty acids (VFAs) for biological nitrogen removal and enhanced biological phosphorous removal has been demonstrated, and these methods have been applied to full-scale WWTPs [3][4][5][6]. Furthermore, previous studies at Klagshamn have shown that the production of hydrolysate with low levels of ammonium and phosphate release provides a high denitrification rate [7] and has no significant effect on the measured gas production [8].…”
Section: Introductionmentioning
confidence: 99%